Hedging devices in Hilary Kilpatrick’s English translation of Ghassan Kanafani’s novel Rijal Fi Ashams / Ibrahim M. I. Alsemeiri - Ibrahim M. I. , Alsemeiri (2018)
This study is essentially projected to explore the process of translating hedges from the Arabic language into the English language in one of Gassan Kanafni’s master pieces “Rijal fi Ashams” and how the hedges forms are affected after the translation and it conveys more commitment or less according to the language culture and system. The novel is considered as a piece of resistance literature and it is translated into the English language by Hilary Klipatrick. The collected data investigates the whole novel which consists of seven chapters in both versions. In this research, two main objectives have been proposed. Firstly, the study attempts to explore the translation procedures that have been employed to translate the Arabic hedges into English. Secondly, it examines the cultural role in translating the Arabic hedges into English. For the sake of collecting and analyzing the hedges in the novel, the current research has applied two translation approaches. Firstly, Hyland’s typology (1998) has been used in order to classify the data from both versions. Secondly, Vinay and Darbelnet’s translation procedures have been applied in order to explore the types of procedures used by the translator in rendering the hedges. The findings of the study have shown that: firstly, the translator tends to use oblique or indirect translation procedures in rendering the vast majority of the hedges in the novel. And, he only uses literal procedures from the direct translation procedures. Secondly, it is evident that culture affectes the degree of commitment and the range numbers of hedges in both languages.